2021
DOI: 10.1136/bmjopen-2021-051874
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study on the characteristics of unrecorded alcohol consumption in nine newly independent states between 2013 and 2017

Abstract: ObjectivesAs unrecorded alcohol use contributes to a substantial burden of disease, this study characterises this phenomenon in newly independent states (NIS) of the former Soviet Union with regard to the sources of unrecorded alcohol, and the proportion of unrecorded of total alcohol consumption. We also investigate associated sociodemographic characteristics and drinking patterns.DesignCross-sectional data on overall and unrecorded alcohol use in the past 7 days from WHO STEPwise Approach to NCD Risk Factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…It is important to highlight opposing judgement of private distillation, since on the one hand it increases the popularity of the drink, but on the other hand quality issues arise. A similar situation can be seen in several countries of Europe or Asia, where various regulations (e.g., restrictions on opening hours) prioritized homemade spirits over their shop counterparts (Skorobogatov, 2014;Manthey et al, 2020;Probst et al, 2021). As in the case of home-distilled pálinka, the quantity and quality of homemade drinks also causes problems in other countries of the word and of the European Union.…”
Section: Typical Characteristicsmentioning
confidence: 68%
“…It is important to highlight opposing judgement of private distillation, since on the one hand it increases the popularity of the drink, but on the other hand quality issues arise. A similar situation can be seen in several countries of Europe or Asia, where various regulations (e.g., restrictions on opening hours) prioritized homemade spirits over their shop counterparts (Skorobogatov, 2014;Manthey et al, 2020;Probst et al, 2021). As in the case of home-distilled pálinka, the quantity and quality of homemade drinks also causes problems in other countries of the word and of the European Union.…”
Section: Typical Characteristicsmentioning
confidence: 68%
“…There exists a misconception that the consumption of unrecorded alcoholic drinks is mainly prevalent in socioeconomically disadvantaged countries. A recent report revealed that an estimated 20 % of the total alcohol consumed in the WHO European region is unrecorded [ 66 ]. Such beverages account for a significant proportion of alcohol consumption in various European countries, including Germany (10.4 %), Croatia (15.7 %), and Greece (41.3 %) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, such incidences of methanol poisoning are often underreported, particularly with emerging online sale of unrecorded alcohols such as homemade, illicit, and surrogate varieties [ 88 ]. Recently, there has been growing apprehension regarding methanol and metal contamination in unrecorded fruit spirits (unregistered alcohols) across the European Union and Asia underscoring the need for a new alcohol regulation [ 66 , 67 , [89] , [90] , [91] ]. Specifically, the methanol, 1-propanol, 1-butanol, 2-butanol, iso-butanol, and isoamyl alcohol levels were found to be notably higher in unrecorded spirits compared to their recorded equivalents across Central and Eastern European countries [ 92 ].…”
Section: Discussionmentioning
confidence: 99%